Hyperhomocysteinaemia and MTHFR C677T gene polymorphism in renal transplant recipients. Issue 1 (1st July 2001) - Szabó, A J; Tulassay, T; Melegh, B; Szabó, T; Szabó, A; Vannay, Á; Fekete, A; Süveges, Z; Reusz, G S
Abstract : AIM: To study the effect of folate treatment on hyperhomocysteinaemia and the effect of 5, 10-methylenetetrahydrofolate reductase (MTHFR) gene polymorphism on total homocysteine and folate concentrations after renal transplantation. METHODS: A total of 30 transplanted children and adolescents were investigated for total homocysteine and folate serum concentrations before and after folate treatment, as well as for the presence of the MTHFR C677T polymorphism. RESULTS: The allele frequency of C677T polymorphism in the MTHFR gene in the study population (0.33) was not different to that in controls (0.38). Before folate treatment the homocysteine concentration was raised in all groups; following folate supplementation it was significantly decreased in the CC and CT groups, but not in the TT group. In patients with CC genotype, serum homocysteine correlated with serum creatinine and cholesterol, and time since transplantation before treatment. CONCLUSION: Folate supplementation appears to be an effective strategy to normalise total homocysteine concentration in renal transplanted children and adolescents.